Role of TLR4 in endoplasmic reticulum stress induced by physical exercise in skeletal muscle - Marafon, Bruno Brieda (2022)
Many conditions can induce endoplasmic reticulum (ER) stress, such as inflammation and physical exercise. Toll-like Receptor 4 (TLR4) can trigger inflammation and ER stress events. However, there are still no data in the literature regarding the role of TLR4 in ER stress during exercise in skeletal muscle. Therefore, the current investigation aimed to verify the responses of ER stress markers in wild-type (WT) and Tlr4 global knockout (KO) mice after acute and chronic physical exercise protocols. Eight-week-old male WT and KO mice were submitted to acute (moderate or high intensity) and chronic (4-week protocol) treadmill exercise. Under basal conditions, KO mice showed lower performance in the rotarod test, and increased eIF2α protein phosphorylation compared to WT animals. Acute moderate-intensity exercise increased BiP and CHOP protein in the WT group. After the acute high-intensity exercise, there was an increase in Casp3 and Ddit3 mRNA for the KO mice. Acute exercise increased the cleaved Caspase-3/Caspase-3 in the KO group regardless of exercise intensity. In response to chronic exercise, the KO group showed no improvement in any performance evaluation. The 4-week chronic protocol did not generate changes in CHOP, p-eIF2α/eIF2α, and cleaved Caspase-3/Caspase-3 ratio but reduced BiP protein compared to the KO-Sedentary group. These results demonstrate that the global deletion of Tlr4 seems to protect the mice against ER stress but decreases their performance. The cleaved Caspase-3/Caspase-3 ratio may be activated by another pathway other than ER stress in Tlr4 KO animals.